The Effect of Tax Avoidance on Cost of Debt with Institutional Ownership as a Moderating Variable (Empirical Study of Energy Sector Companies Listed on The IDX 2020-2022) - Utami, Laila Dyah; Pramiana, Omi (International Journal of Pertapsi, 2024)
This research aims to test the effect of tax avoidance on the cost of debt with institutional ownership as a moderating variable. In this research, tax avoidance is measured by the effective tax rate. The population in this research is energy sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This type of research is quantitative research. The sample in this research was obtained using purposive sampling, namely selecting samples using predetermined criteria. Based on the purposive sampling method, 57 samples were obtained from 82 energy sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The analytical methods used are simple linear regression analysis, Moderated Regression Analysis, partial test (t), and coefficient of determination test (R2) using the SPSS version 16 program. The results of this research show that tax avoidance has a significant negative influence on cost of debt. Institutional ownership can strengthen the tax avoidance and cost of debt variables.